Quantitative analysis of urinary acylglycines for the diagnosis of beta-oxidation defects using GC-NCI-MS - Costa, CG (2015)
The analysis of acylglycines is an important biochemical tool for the diagnosis of inherited disorders of mitochondrial fatty acid P-oxidation. A stable isotope dilution gas chromatography negative chemical ionisation mass spectrometry method for the quantitative analysis of short and medium-chain acylglycines as their bis(trifluoromethyl)benzyl (BTFMB) ester derivatives is described. The diagnostic usefulness of the method was demonstrated in nine patients with medium-chain acyl-coenzyme A (CoA) dehydrogenase (MCAD) deficiency, and seven patients with multiple acyl-CoA dehydrogenation defect (MAD). The urinary acylglycine profiles in these patients were compared to those in controls (n = 19), children on a medium-chain triglyceride (MCT) supplemented diet (n = 4), and patients with various other diseases (n = 5). (C) 2000 Elsevier Science B.V. All rights reserved.